Perawatan Tradisional Ata Pesi pada Era Kesehatan Modern di Tueng - Jaya, Hilda; Sudiarna, I Gusti Putu; Murniasih, Anak Agung Ayu (Department of Anthropology Udayana University, 2023)
Research related to traditional or pesi care in the Tueng Village community was studied by applying the theory of the Foster & Anderson medical system and the theory of the Hierarchy of resort Romanucci-Ross. The concept used as a reference in this research is the ata pessi and modern health. The method used is a qualitative research method, by collecting data including the determination of informants, observations, interviews, literature studies, and data analysis. The results showed that the people of Tueng Village still carried out pregnancy and childbirth care by ata pesi. This is influenced by the community's view of ata pesi which is inseparable from the socio-cultural life of the local community. There is also the process and mechanism of traditional ata pesi care in assisting the delivery process, namely, first or pesi doing cikeng, second entap wall, third poro putes, fourth cear sumpe ceremony. Factors that influence people still maintain traditional or pessary care, among others, distance, economic affordability, cultural similarities, hereditary factors.